Development of Maternal Health Literacy Measurements: A Scoping Review - Putri, Anggie Pradana; AM., Ady Irawan; Lu, Yu Ying (Alta Dharma Publisher, 2023)
Background: Maternal health literacy (MHL) is essential in identifying pregnant women with limited MHL, especially in the post-COVID-19 period. The data can assist in the design of tailored interventions for improving MHL. Nevertheless, MHL measurements are not routinely applied because more general health literacy scales are used to assess MHL in pregnancy. Objective: This study aimed to provide an overview of MHL measurement development. Method: A scoping review was utilized in this study. The search was conducted through four electronic databases (CINAHL, PubMed, Web of Science, and Science Direct) published in English and Indonesian between 2001 to 2021, with the searching process of PCC (Population: pregnant women, Concept: maternal health literacy instrument development, Context: clinical or community setting). The selection process of the articles is referred to as Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Result: The selected articles' critical appraisal was done using The Joanna Briggs Institute Checklist. The measurements of MHL are Maternal Health Literacy and Pregnancy Outcome Questionnaire (MHLAPQ), Maternal Health Literacy (MaHeLi), and Maternal Health Literacy Inventory in Pregnancy (MHELIP). These instruments are adequate, valid, and reliable. The MHELIP is the fittest instrument to capture the MHL concept because it consists of specific items to measure MHL in pregnancy. Future studies must investigate this topic as thoroughly as the current material available in some databases. In addition, healthcare practitioners can apply the MHL in pregnancy measurement to analyze and report client cases, contributing to the expansion of MHL's body knowledge.